SAE Technical Paper Series 2015
DOI: 10.4271/2015-24-2408
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis of the Effects of Fuel Composition and Injection Strategy on Mixture Preparation and Fuel Deposit Formation in a GDI Engine

Abstract: In spark-ignited direct-injected engines, the formation of fuel pools on the piston is one of the major promoters of unburnt hydrocarbons and soot: in order to comply with the increasingly stringent emission regulations (EU6 and forthcoming), it is therefore necessary to limit fuel deposit formation. The combined use of advanced experimental techniques and detailed 3D-CFD simulations can help to understand the mechanisms driving fuel pool formation. In the paper, a combined experimental and numerical character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In recent years there have been significant developments in accurate 3D CFD modelling of GDI engines as this offers a useful insight into the physico-chemical mechanisms leading to particle formation. Several studies [25,38,39] demonstrated that a strong indirect correlation exists between mixture preparation and engine-out PN Den . Engine speed, injection timing and mixing time are shown to influence the preparation process, but injection pressure appears to be the most significant driver for mixture homogeneity.…”
Section: Computational Fluid Dynamics Analysis Of Mixture Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years there have been significant developments in accurate 3D CFD modelling of GDI engines as this offers a useful insight into the physico-chemical mechanisms leading to particle formation. Several studies [25,38,39] demonstrated that a strong indirect correlation exists between mixture preparation and engine-out PN Den . Engine speed, injection timing and mixing time are shown to influence the preparation process, but injection pressure appears to be the most significant driver for mixture homogeneity.…”
Section: Computational Fluid Dynamics Analysis Of Mixture Preparationmentioning
confidence: 99%
“…Control strategies which include high injection pressure and appropriate timing to minimise unwanted jet-to-wall impact are seen to be potentially beneficial across the wider engine running envelope. Through modelling of a high-performance wall-guided GDI engine, Giovannoni et al [25] showed how retarded SOI increases the quantity of fuel film forming on the piston crown, resulting in an unwanted stratification of the equivalence ratio distribution across the entire combustion chamber. Importantly, the study demonstrates that exhaust soot concentration is intimately correlated with the summation of combustion chamber computational cells' mass, where the modelled fuel equivalence ratio at ignition timing is in excess of a set rich threshold.…”
Section: Computational Fluid Dynamics Analysis Of Mixture Preparationmentioning
confidence: 99%
See 3 more Smart Citations